Residual γH2AX foci predict local tumour control after radiotherapy - Koch, Ulrike; Höhne, Katharina; Neubeck, Cläre von; Thames, Howard D.; Yaromina, Ala; Dahm-Daphi, Jochen; Baumann, Michael; Krause, Mechthild (Radiotherapy and oncology, 2013)
Purpose - Evaluation of micromilieu-dependent quantified γH2AX foci as a potential predictive biomarker in well-oxygenated tumour areas in 9 HNSCC xenograft models in vivo. - Materials & methods - GammaH2AX foci were quantified in perfused tumour areas 30min (initial γH2AX foci) and 24h (residual γH2AX foci) after exposure to a single dose of 4Gy. The initial and residual normalised γH2AX foci were correlated with TCD50 after single dose irradiation under clamped blood flow (SDclamp) or a fractionated irradiation setting under ambient blood flow (fx). - Results - A significant negative correlation between initial and residual normalised γH2AX foci and TCD50 SDclamp and TCD50 fx for 9 HNSCC tumour xenograft models in vivo was found. Residual normalised γH2AX foci showed higher intertumoural variability and their correlation with TCD50 was more robust. - Conclusions - For the first time a significant negative correlation between γH2AX foci and local tumour control after irradiation has been demonstrated. Our results underline the potential of residual γH2AX foci as a predictive biomarker for local tumour control after radiotherapy.
Gesehen am 17.12.2021